Secured Cotabato City State Polytechnic College Web-Based Student Clearance System - Guiamarudin S Daud; Mohaymin A. Maguid (RIRAI Publisher, 2022)
The study describes the Secured CCSPC Web-Based Student Clearance System's use and predicted effects. Hypertext Transfer Protocol (HTTP), Hypertext Preprocessor (PHP), Sublime editor, Bootstrap, and MySQL as the database tool were used to create the clearance system. This system includes two-factor authentication for students and designated offices. In the clearance system, a Secure Socket Layer (SSL) for data transit, as well as a software firewall and anti-SQL Injection attack, were offered and implemented. The CCSPC Portal was linked to the web-based student clearance system and Web API, with Web API acting as a bridge between SIMone and the clearance system. SIMone's role is to offer just a limited amount of information on the web-based clearing, such as designated office operations, account status from the Cashier, and student profiles from the Registrar. Students and the approved offices in charge of signing the student clearance include the Graduating Class Association (GCA) Treasurer, Laboratory Custodian, Cashier, Librarian, Academic Related Services (ARS), SPEED Director, Department Chairperson, College Dean, and the Registrar. The ISO 9126-1 International Standard Tool for Software Evaluation, on the other hand, was utilized in the CCSPC beneficiaries' surveys to test the system's effectiveness and reliability.